Reliability and rapid analysis method of plasma busulfan by solid phase extraction gas chromatography-mass spectrometry - tummarintra, Paiboon; Kriengsoontornkij, Worapant (Archives of Allied Health Sciences, 2019)
Busulfan is an alkylating agent used in combination with cyclophosphamide as a conditioning agent prior to bone marrow transplantation. Therapeutic drug monitoring and dose adjustment are currently used to optimize and individualize therapy with busulfan. The reliability and rapid analysis method of plasma busulfan are important. GC-MS assay method was developed and validated for the determination of plasma busulfan. Busulfan was extracted from plasma samples and derivatized with NaI2 prior to GC-MS determination. The Solid Phase Extraction (SPE) was used for extraction. The method was developed and fully validated according to USFDA guideline. The limit of quantification (LOQ) was 10 ng/mL for busulfan. The method was fully validated in terms of selectivity, accuracy, precision, linearity (r2>0.9994) and stability. The recoveries of extraction ranged from 99.65-100.19% with repeatability. A rapid, sensitive, accurate and reproducible of GC-MS method for quantification of busulfan plasma levels were developed and validated, suggesting that this method could be used for routine analysis.